The Study of Creative Thinking Skills And Learning Achievement Using Creative Based Learning With The Team-Pair-Solo Technique In S14101 Social Studies For Grade 4 Students - Phothibundit, Arkaradet; Tungkasamit, Angkana (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were to 1) study creative thinking skills using a Creative Based learning with.Team-pair-solo techniques subject S14101 Social Studies for Grade 4 students has a score of 70 percent or more. 2) Study academic achievement using a The Study of Creative Thinking Skills And Achievement Using Creative Based Learning With The Team-Pair-Solo Technique subject S14101 Social Studies for Grade 4 70 percent of the students has a score of 70 percent or more. This research is a pre experimental design (one shot case study) The target group in this research is 4th grade students of Ban Ped School (Tha Bueng Pracha Songkhro) who are studying in the second semester of the academic year 2024, totaling 28 people. The research tools used Including 1) a learning management plan using a creative learning management model as a base together with Team-pair-solo, 8 plans 2) Creativity test, 16 questions 3) Academic achievement test, 40 questions. Statistics used in data analysis are mean, standard deviation and percentage. The research results found that 1. The creative thinking skills of the 4th grade students of Ban Ped School (Tha Bueng Prachasongkhro) after the number of students who passed the criteria, 27 out of 28 students, representing 96.43 percent, and had an average score of 43.25, representing 90.10 percent, which is lower than the specified criteria. 2. Academic achievement: The number of students who passed the criteria was 22 out of 28 students, which is 78.57 percent, and the average score was 31.35, which is 78.37 percent, which is higher than the specified criteria